Planned cesarean delivery compared to induction of labor in women with class III obesity: a cost-minimization analysis. (1st October 2016) - Subramaniam, Akila; Corvey, Kathryn J.; Kilgore, Meredith L.; Edwards, Rodney K.
Abstract: Objective : To compare the costs between planned cesarean delivery (CD) and induction of labor (IOL) in women with class III obesity. Methods : We conducted a cost-minimization analysis using data from a previous study of women with a BMI ≥40 kg/m 2 delivering term singletons via planned CD or after IOL. Decision trees were built with branches for two "treatments": planned CD and IOL (probabilities derived from parent study). Direct and total costs were obtained for each mother–infant pair. Sensitivity analyses for probability of successful IOL were performed. Results : A total of 661 mother–infant pairs were included – 399 IOLs and 262 planned CDs. Of 399 IOLs, 236 (59%) delivered vaginally and 163 (41%) had a CD. IOL was slightly less costly. For IOL and planned CD, respectively, direct costs were $7416 versus $7474, and total costs were $11 545 versus $11 665. Sensitivity analyses indicated that IOL was the least costly strategy if the probability of vaginal delivery after IOL was >57% (0.575 for direct costs; 0.570 for total costs). There was, however, a slight cost advantage to planned CD in women with a prior cesarean. Conclusions : In women with class III obesity, IOL is less costly than planned CD if the probability of vaginal delivery after IOL in an individual patient is greater than 57%.